2018
DOI: 10.1111/bcp.13787
|View full text |Cite
|
Sign up to set email alerts
|

The effect of indapamide vs. bendroflumethiazide for primary hypertension: a systematic review

Abstract: The aims of the current review were to compare the efficacy of monotherapy with bendroflumethiazide vs. indapamide on mortality, cardiovascular outcomes, blood pressure, need for intensification of treatment and treatment withdrawal. Two authors independently screened the results of a literature search, assessed the risk of bias and extracted relevant data. Randomized clinical trials of hypertensive patients of at least a 1‐year duration were included. When there was disagreement, a third reviewer was consulte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 56 publications
(98 reference statements)
0
12
0
Order By: Relevance
“…Herein, we can understand the mechanisms of the drugs which were predicted in the present study based on the above discussion. Trichlormethiazide and bendroflumethiazide are both inhibitors for CAs [90,91]. Application of CA inhibitors in COVID-19 individuals can block the discharge of H+ in the kidney and worsen the acidotic status in patients [92].…”
Section: Discussionmentioning
confidence: 99%
“…Herein, we can understand the mechanisms of the drugs which were predicted in the present study based on the above discussion. Trichlormethiazide and bendroflumethiazide are both inhibitors for CAs [90,91]. Application of CA inhibitors in COVID-19 individuals can block the discharge of H+ in the kidney and worsen the acidotic status in patients [92].…”
Section: Discussionmentioning
confidence: 99%
“…perpetuity. preprint (which was not certified by peer review) is the author/funder, who has granted medRxiv a license to display the preprint in The copyright holder for this this version posted August 25, 2021. ; https://doi.org/10.1101/2021.08.19.21262289 doi: medRxiv preprint recent meta-analysis by our group, whilst highlighting the need for further research, demonstrated no difference in outcomes between indapamide and bendroflumethiazide (16).…”
Section: Rationale For Evidencementioning
confidence: 75%
“…[33] In this study, 20% patient were detected obese (Table 3). Peart SS et al [34] had shown that the obesity has significant contribution to the risk of stroke of untreated patient of either sex. So findings in this study correlate well with above mentioned study.…”
Section: Discussionmentioning
confidence: 99%